ABDOMINAL COCOON SYNDROME: A CASE REPORT - Khanzada, Khizar Hayat; Butt, Mariya Rizwan; Khalid, Komal; Ahmad, Husnain (Journal of Ayub Medical College Abbottabad, 2026)
Abstract INTRODUCTION: Abdominal cocoon syndrome is an unusual cause of small bowel obstruction characterized by encasement of the bowel by a fibrous and/or collagenous membrane. PRESENTATION OF CASE: A 38-year-old male, with no comorbidities, presented with signs and symptoms of sub-acute intestinal obstruction for the last one and a half months. He had two episodes of similar symptoms in the past year. DISCUSSION: It is a rare disease. Patients usually present with symptoms of recurrent obstruction of the small bowel, usually without any obvious cause. The preferred imaging modality is a CT scan however diagnosis is usually made intra-operatively. Surgical excision of membranes carries a good prognosis. CONCLUSION: Abdominal cocoon syndrome is a rare cause of obstruction of the small bowel where preoperative diagnosis usually is difficult. Treatment of choice is meticulous surgical excision of the membranes.